2018
DOI: 10.3842/sigma.2018.044
|View full text |Cite
|
Sign up to set email alerts
|

The q-Onsager Algebra and the Universal Askey-Wilson Algebra

Abstract: Recently Pascal Baseilhac and Stefan Kolb obtained a PBW basis for the q-Onsager algebra O q . They defined the PBW basis elements recursively, and it is obscure how to express them in closed form. To mitigate the difficulty, we bring in the universal Askey-Wilson algebra ∆ q . There is a natural algebra homomorphism : O q → ∆ q . We apply to the above PBW basis, and express the images in closed form. Our results make heavy use of the Chebyshev polynomials of the second kind.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…(i) We invoke Proposition 3.9. For notational convenience we identify the algebras U + q and U, via the isomorphism ♮ from below (15). Let Ω denote the set of alternating words listed in (71).…”
Section: The Alternating Pbw Basis For Umentioning
confidence: 99%
See 1 more Smart Citation
“…(i) We invoke Proposition 3.9. For notational convenience we identify the algebras U + q and U, via the isomorphism ♮ from below (15). Let Ω denote the set of alternating words listed in (71).…”
Section: The Alternating Pbw Basis For Umentioning
confidence: 99%
“…The following results can be obtained using Lemma 5.9 and induction on n. The proofs are straightforward and omitted. [2], [13], [14], [15], [16], [18] might be helpful in this direction. Problem 13.4.…”
Section: Comparing the Damiani Pbw Basis And The Alternating Pbw Basismentioning
confidence: 99%
“…These expressions resemble the usual Lie bracket in the associative algebra, which is [U, V ] := U V − V U . Some specific examples are the quantum group U q (sl 2 ) in its "equitable presentation" [16], the Fairlie-Odesskii algebra U q (so 3 ) in its usual presentation [10,11,12,15], the parametric family of Askey-Wilson algebras [18,19], and the parametric family of q-deformed Heisenberg algebras [13,14] whose defining relations are q-deformations of the Heisenberg-Weyl relation.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, even if the defining relations of an associative algebra involve deformed commutation relations, it is still possible to compute Lie polynomials in the generators of the algebra. This notion first appeared in [18,Problem 12.14] for the universal Askey-Wilson algebra. It was found that the defining relations in this algebra and This work was partially supported by a grant from De La Salle University, Manila, and also by a grant from the Commission for Developing Countries of the International Mathematical Union (IMU-CDC).…”
Section: Introductionmentioning
confidence: 99%
“…Further applications arise in the theory of special functions [4,23], tridiagonal and Leonard pairs [24,27], superintegrable quantum systems [3] and the reflection equation [2]. Its use to quantum mechanics is further emphasized by its identification as a quotient of the q-Onsager algebra [26], which originates from statistical mechanics. Furthermore, AW (3) has arisen as the spherical subalgebra of the double affine Hecke algebra of type (C ∨ 1 , C 1 ) [22,20].…”
Section: Introductionmentioning
confidence: 99%